EXPERIENCE REPORT OF A SCHOOL PROJECT: HEALTH EDUCATION AND IMMUNIZATION STRATEGIES AGAINST DENGUE (CIPEEX, 2025)
Health education acts as an essential tool in health promotion, empowering people to adopt preventive practices that ensure safety and well-being, both individually and collectively. This educational process is fundamental for building a more conscious and healthy society. Dengue is a serious viral disease, and immunization is one of the main strategies for its control. Objective: To promote awareness of the importance of safe vaccination using interactive and playful teaching methods. Methodology: An illustrative lecture on the symptoms and prevention of dengue was given, followed by discussion groups and thematic activities to reinforce the children's learning. Interactive games were used to assess the students' understanding. Results: The playful activities facilitated the children's assimilation of the content, highlighting the effectiveness of interactive methodologies in health education. Conclusion: Adapting teaching methodologies to the age group of the target audience is crucial for the success of health education projects, suggesting that interactive and participatory approaches are essential for engagement and understanding of complex topics such as immunization against dengue fever.
Keywords: Immunization; Dengue; Patient Safety; Health Education